Inhibition of farnesyl pyrophosphate synthase prevents angiotensin II‐induced cardiac fibrosis in vitro. (June 2014) - Li, Z.; Bi, X.; Wang, M.; Zhang, J.; Song, J.; Shen, X.; Han, J.; Fu, G.; Ye, Y.
Summary Farnesyl pyrophosphate synthase (FPPS)‐catalysed isoprenoid intermediates are important for the activation of Ras homologue gene family, member A (RhoA) in angiotensin (Ang) II‐induced cardiac fibrosis. This study was designed to investigate the specific role of FPPS in the development of cardiac fibrosis. We demonstrated that FPPS expression was elevated in both in‐vivo and in‐vitro models of Ang II‐mediated cardiac fibrosis. FPPS inhibition by zolendronate and FPPS knock‐down by a silencing lentivirus decreased the expression of cardiac fibrosis marker genes, including collagen I, collagen III and transforming growth factor (TGF)‐β1. FPPS inhibition was reversed by geranylgeraniol (GGOH) and mimicked by RhoA knock‐down with siRhoA. The antagonistic effect of GGOH on the zolendronate‐mediated modulation of RhoA activation in Ang II‐stimulated cardiac fibroblasts was demonstrated by a pull‐down assay. Furthermore, FPPS knock‐down also prevented RhoA activation by Ang II in vitro. In conclusion, FPPS and RhoA may be part of a signalling pathway that plays an important role in Ang II‐induced cardiac fibrosis in vitro.